2008
DOI: 10.1287/inte.1080.0367
|View full text |Cite
|
Sign up to set email alerts
|

The “Killer Application” of Revenue Management: Harrah's Cherokee Casino & Hotel

Abstract: Harrah's Cherokee Casino & Hotel is an unusual example of the use of revenue-management (RM) techniques. Typical RM installations yield revenue improvements of between 3 and 7 percent. The Harrah chain has seen 15-percent improvements, with Harrah's Cherokee Casino & Hotel as the largest beneficiary-although it does not serve alcohol or have traditional table games. In addition, the RM techniques that the Cherokee uses, such as its pricing decisions and customer-segmentation rules, are different from those use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Failure to consider the order's capacity consumption and resulting effects on the bottlenecks in the production stream may lead to losses in capacity and inefficient order acceptance decisions. In similar settings in the service industry, RM has significantly contributed towards improved order acceptance decisions (Cross 1997;Metters, Queenan, Ferguson, Harrison, Higbie, Ward, Barfield, Farley, Kuyumcu, and Duggasani 2008;Geraghty and Johnson 1997). Hence, implementing RM in the above-described setting promises great potential which will be further explained with details from practice in section 4.…”
Section: Make-to-order Steel Manufacturingmentioning
confidence: 98%
See 1 more Smart Citation
“…Failure to consider the order's capacity consumption and resulting effects on the bottlenecks in the production stream may lead to losses in capacity and inefficient order acceptance decisions. In similar settings in the service industry, RM has significantly contributed towards improved order acceptance decisions (Cross 1997;Metters, Queenan, Ferguson, Harrison, Higbie, Ward, Barfield, Farley, Kuyumcu, and Duggasani 2008;Geraghty and Johnson 1997). Hence, implementing RM in the above-described setting promises great potential which will be further explained with details from practice in section 4.…”
Section: Make-to-order Steel Manufacturingmentioning
confidence: 98%
“…Further, practical examples for the difficulty of applying a deterministic model in m-t-o steel manufacturing are given in the following section. The DLP's popularity in practical applications results from its efficient computational solving and that even though it is simple, it has a relatively good performance rating (compare the results of Metters, Queenan, Ferguson, Harrison, Higbie, Ward, Barfield, Farley, Kuyumcu, and Duggasani 2008). This is the case when frequent re-optimization is undertaken (Talluri and van Ryzin 2004).…”
mentioning
confidence: 99%
“…[60]. Metters et al [61] discuss another successful casino implementation where indirect revenues are considered for the allocation of rooms. Vinod [62] presents the paradigm of customer-centric RM 1 and conceptualizes strategic approaches for customerbased forecasting, product unbundling, and fare management.…”
Section: Related Literaturementioning
confidence: 99%
“…Thus, by means of loyalty cards (see casino hotels in Metters et al, 2008), Customer value-based airline revenue management individual tariff verification cards (see drivers of parking lots in Guadix et al, 2009) and individual subscription contracts (see opera and arts companies in Ovchinnikov et al, 2014), clients can be unequivocally identified at the time of request and customer behaviour can be tracked and then used to forecast customer lifetime value. Other authors assume that the customer's membership in a defined segment can be clearly determined (see unambiguous classification to segments with averaged lifetime values for an airline provider in von Martens and Hilbert, 2011).…”
Section: Classification Of Customersmentioning
confidence: 99%